The Organizational Climate Development in the Light of Job Stress Treatment: A Field Study in Governmental Sheltered Accommodation Houses in the Ministry of Labour and Social Affairs - الجادر, سهير عادل; الحمداني, الهام محمد (Journal of Economics and Administrative Sciences, 2014)
Job stress is considered one of the most important obstacles that may appear in the work field. In order to deal with the obstacles and challenges , the idea to deal with job stress has come to address job stress as one of the most important trends that enable organizations to face those challenges through focusing on the role of job stress and the organizational climate of the organization.        The research deals with two variables: the job stress as an independent variable, and the organizational climate as a dependent one. Each variable includes five sub-dimensions. These dimensions have been involved in an interaction to form the framework of this research. The research aims to define the impact of the job stress as an independent variable, on the dependent variable, organizational climate in the service sector which represents one of the most important bases of the state society and its development through presenting social-service activities including those presented to the orphans, the handicapped and the elderly. The research has adopted the analytic descriptive approach. The data have been collected from (125) employees working in six of the sheltered accommodation houses (Ederly-care house, Alhanan house for severely-handicapped Children, Braum Al-Wazeriya Orphanage in Wazeriya, Zhour Al-Dameia Orphanage in Al-Dameia, Al-Alweya'a Orphanage in Al- Alweya's, Childhood House in Alsalehya. The questionnaire method has been used as a main tool for collecting the data besides the personal interviews and pamphlets issued by these accommodation houses. In order to process the data, many statistical methods have been used including  arithmetic mean, standard deviation, percentages, coefficient, and the Kruskel- Wallis. Based on the measurement of the research variables and diagnosis of the relations of correlation and impact, the research has reached a number of conclusions whose most important one is that there is no correlation and impact relations between the job stress and the organization climate in the sheltered accommodation houses. On the other hand, the difference-test has showed that there are value differences at all the sheltered accommodation houses.       The researcher has provided a number of recommendations including the need of the studied sheltered accommodation houses to adopt the job description process as well as increasing the attention paid to the human resources and developing  and rehabilitating their physical and intellectual capacities through continuous training and enhancing the possibilities required for achieving this goal through studying need analysis on objective grounds.